2018
DOI: 10.1080/15538362.2018.1502723
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Diversity in Robusta Coffee Using Morphological Characters

Abstract: Assessing the level of genetic variation that exist in any breeding population is important as this has significant implications for selection and variety development. The objectives of the present study were to determine the variation among 71 Robusta coffee genotypes based on 21 traits and to determine the genetic relationships between the genotypes. The 71 genotypes were established in 2013 as clones raised from single node cuttings and planted in a randomized complete block design with four blocks, with fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…Genetic variability and estimation of genetic parameters of key productivity traits are of significant importance to guide selection in a hybrid breeding programme. Though the gene pool of Robusta coffee in Ghana based on morphological characters has been determined to be narrow (Akpertey et al, 2018b), the results from the present study indicated the presence of variation among the families for most vegetative growth traits and all yield traits, based on which significant improvement could be made in the breeding of the crop in the country. The presence of the significant variation may be attributed to the larger number of families included in the study.…”
Section: Discussionmentioning
confidence: 52%
“…Genetic variability and estimation of genetic parameters of key productivity traits are of significant importance to guide selection in a hybrid breeding programme. Though the gene pool of Robusta coffee in Ghana based on morphological characters has been determined to be narrow (Akpertey et al, 2018b), the results from the present study indicated the presence of variation among the families for most vegetative growth traits and all yield traits, based on which significant improvement could be made in the breeding of the crop in the country. The presence of the significant variation may be attributed to the larger number of families included in the study.…”
Section: Discussionmentioning
confidence: 52%
“…We need to select the varied progenies of crosses for superior planting materials. Observing the agronomic character is crucial in supporting the success of a plant breeding program (Akpertey et al, 2019). For example, leaf size is related to plant adaptability and photosynthetic efficiency, while internode length can be used to estimate coffee productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Gene bank activities may be affected by improper identification, redundancy, and other errors because the trees in the germplasm plots were collected, exchanged, or otherwise obtained at different times with limited passport data on their correct identity. Moreover, limited knowledge on the level of genetic diversity of the C. canephora germplasm hinders their effective utilization in a breeding program ( Akpertey et al, 2019 ). Previous efforts on genotype identification and diversity assessment in the coffee germplasm collections in Ghana have relied largely on morphological characters ( Anim-Kwapong et al, 2010 ; Akpertey et al, 2019 ), which is limited because the environment tends to have a significant effect on phenotypic expression ( Souza et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, limited knowledge on the level of genetic diversity of the C. canephora germplasm hinders their effective utilization in a breeding program ( Akpertey et al, 2019 ). Previous efforts on genotype identification and diversity assessment in the coffee germplasm collections in Ghana have relied largely on morphological characters ( Anim-Kwapong et al, 2010 ; Akpertey et al, 2019 ), which is limited because the environment tends to have a significant effect on phenotypic expression ( Souza et al, 2013 ). Precise identification of plants in any germplasm collection is important to facilitate its management and utilization.…”
Section: Introductionmentioning
confidence: 99%